2020
DOI: 10.1109/access.2020.3010852
|View full text |Cite
|
Sign up to set email alerts
|

Extracting User-Centric Knowledge on Two Different Spaces: Concepts and Records

Abstract: The growing demand for eliciting useful knowledge from data calls for techniques that can discover insights (in the form of patterns) that users need. Methodologies for describing intrinsic and relevant properties of data through the extraction of useful patterns, however, work on fixed input data, and the data representation, therefore, constrains the discovered insights. In this regard, this paper aims at providing foundations to make the descriptive knowledge that is extracted by pattern mining more user-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Since the early 90s, when the market basket problem was proposed to discover what items were bought together in a transaction, many studies have contributed to an improvement of the efficiency [21] and expressiveness [22] of the proposals. Sequence analysis techniques [11] are some examples of highly expressive proposals required when the sequential order of the items is critical.…”
Section: Related Workmentioning
confidence: 99%
“…Since the early 90s, when the market basket problem was proposed to discover what items were bought together in a transaction, many studies have contributed to an improvement of the efficiency [21] and expressiveness [22] of the proposals. Sequence analysis techniques [11] are some examples of highly expressive proposals required when the sequential order of the items is critical.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the pattern is considered a good descriptor of intrinsic and important properties of the data [7]. These patterns should be novel, significant, unexpected, nontrivial and actionable [8].…”
Section: Related Workmentioning
confidence: 99%
“…Interestingness quality measures of frequent itemsets and association rules should be used to filter, rank and mainly getting more useful results. These measures can be divided into objective or data-driven (statistical and structural properties of data) and subjective or user-driven (user's preferences and goals) [8]. As a result of the related paper review, interestingness, comprehensibility, and usefulness of the found rule or frequent itemset represent the main qualitative characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…In general terms, a pattern (itemset) is the key element in any process of eliciting useful knowledge [14] since it defines subsequences or substructures representing any type of homogeneity and regularity in data [7]. Formally, given a set of items I = {i 1 , i 2 , .…”
Section: Preliminariesmentioning
confidence: 99%